VODKA-JWST: Synchronized Growth of Two Supermassive Black Holes in a Massive Gas Disk? A 3.8 kpc Separation Dual Quasar at Cosmic Noon with the NIRSpec Integral Field Unit - Ishikawa, Yuzo; Zakamska, Nadia L.; Shen, Yue; Liu, Xin; Chen, Yu-Ching; Hwang, Hsiang-Chih; Vayner, Andrey; Rupke, David S. N.; Veilleux, Sylvain; Wylezalek, Dominika; Gross, Arran C.; Sankar, Swetha; et al. (The Astrophysical journal, 2025)
The search for dual supermassive black holes (SMBHs) is of immense interest in modern astrophysics. Galaxy mergers may fuel and produce SMBH pairs. Actively accreting SMBH pairs are observed as dual quasars, which are vital probes of SMBH growth. Dual quasars at cosmic noon are not well characterized. Gaia observations have enabled a novel technique to identify dual quasars at kiloparsec scales based on the small jitters of the light centroid as the two quasars vary stochastically. We present the first detailed study of a z = 2.17, 0 . ″ 46, 3.8 kpc separation dual quasar, J0749+2255, using JWST/NIRSpec integral field unit spectroscopy. Identified by Gaia, J0749+2255 is one of the most distant small-separation dual quasars known. We detect the faint ionized gas of the host galaxy, traced by the narrow H α emission. Line ratios indicate ionization from the two quasars and from intense star formation. Spectral analysis of the two quasars suggests that they have similar black hole properties, hinting at the possible synchronized accretion activity or lensed quasar images. Surprisingly, the ionized gas kinematics suggest a rotating disk rather than the disturbed system expected in a major gas-rich galaxy merger. Numerical simulations show that this is a plausible outcome of a major gas-rich galaxy merger several tens of Myr before coalescence. Whether J0749+2255 reflects an interesting phase of dual quasar evolution or is a lensed quasar remains unclear. Thus, this study underscores the challenges in definitively distinguishing between dual and lensed quasars, with observations supporting either scenario.